2021
DOI: 10.1155/2021/9987141
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Is Common in Ghana despite Abundance of Sunlight: A Multicentre Comparative Cross-Sectional Study

Abstract: Background. Vitamin D is a steroid hormone important for the normal functioning of the body. It is produced through skin exposure to sunlight and from the diet. Although Ghana is located in the tropics where sunlight is abundant, factors like culture, diet, skin pigmentation, variation in the ozone layer, and geographical area influence the optimization of vitamin D concentration. It is imperative to evaluate the interplay between sunshine exposure, proinflammatory cytokines, and mediators of vitamin D metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
1
7
2
Order By: Relevance
“…The observed finding of no statistically significant difference in the serum levels of Vitamin D between RA patients and controls confirms a previous study by Sakyi et al, 13 who found a high prevalence of 25-hydroxyvitamin D deficiency among the general adult population in Ghana despite the abundance of sunlight. This could be attributed to dietary deficiencies and other related considerations of the general population.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The observed finding of no statistically significant difference in the serum levels of Vitamin D between RA patients and controls confirms a previous study by Sakyi et al, 13 who found a high prevalence of 25-hydroxyvitamin D deficiency among the general adult population in Ghana despite the abundance of sunlight. This could be attributed to dietary deficiencies and other related considerations of the general population.…”
Section: Discussionsupporting
confidence: 90%
“…This could be attributed to dietary deficiencies and other related considerations of the general population. 13 Proinflammatory cytokines including TNF-α, IL-1β, IL-6, and IFN-γ play a significant role in the pathogenesis of RA. These cytokines act synergetically leading to an increase in the rate of leukocyte recruitment to the joints, where, they maintain chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations